An Environmental Scan of Programs and Services for Families of Veterans With Operational Stress Injuries. (1st October 2016) - Tam-Seto, Linna; Cramm, Heidi; Norris, Deborah; Eichler, Maya; Smith-Evans, Kimberley
ABSTRACT: This study identifies and describes currently available programs and services for families who have a veteran family member living with Operational Stress Injuries (OSIs). An environmental scan was completed of web-based program information for familial OSI supports. Resources were reviewed and informed a SWOT (strength, weakness, opportunity, and threat) analysis. The study accessed 278 sources. Sixty-six resources met inclusion criteria, including 19 from Canada, 24 from the United States, 15 from the United Kingdom, and eight from Australia. Most resources are for active military members or veterans. Resource descriptions indicate a range of formats and intended family members. Existing resources are often embedded in supporting daily military life rather than issues related to life with OSIs, which may decrease efficacy of OSI-specific interventions. Information on evaluation and evidence for resources is also limited. Due to geographical challenges, there is a call for increasing use of technology to address equitable access.